Provenance discrimination of the clay sediment in the western Taiwan Strait and its implication for coastal current variability during the late-Holocene. (January 2017) - Chen, Jing; Ma, Junqiang; Xu, Kehui; Liu, Yan; Cao, Wenhong; Wei, Taoyuan; Zhao, Baocheng; Chen, Zhongyuan
This study aims to quantify the contribution of Yangtze clays to the sediment accumulation in the western Taiwan Strait and reconstruct the strength of Chinese Coastal Current (CCC) since middle-Holocene driven by East Asian Winter Monsoon (EAWM). Both down-core and surficial sediment samples were collected for grain size, radiocarbon, and clay mineral analyses. One 250-cm-long core was collected from the southern Yangtze distal mud wedge in western Taiwan Strait which receives Yangtze-derived clays transported by the Zhejiang-Fujian Coastal Current (ZFCC), the southern part of CCC. Clay minerals were examined in surficial sediment samples which were influenced by the Yangtze, Zhejiang-Fujian, western Taiwanese rivers, and the inner-shelf mud wedge. Ternary diagrams of smectite–kaolinite–chlorite revealed that three endmembers represented the Yangtze, Min, and western Taiwanese rivers, respectively. The estuaries seaward of the tidal current limits of Zhejiang-Fujian rivers, especially the Qiantang and Ou, were influenced by Yangtze-derived sediments through energetic tidal mixing. It was found that smectite can be used as a fingerprint of the Yangtze fine-grained sediment because among all the studied rivers, the Yangtze is the only one supplying smectite. Clay mineral results in core sediments revealed a dramatic provenance change at the depth of 113 cm, dated at ~4.0 cal. kyr BP. Smectite disappeared in the upper core, suggesting decreased contribution of Yangtze clays to the southern distal mud wedge. Decreased grain size of the fine population in the upper core also indicated that the ZFCC weakened during the late-Holocene. Such a decline also occurred in Subei Coast Current (northern part of CCC), revealed by the previous studies. The decline of CCC was related to the decreased EAWM of the late-Holocene, and it resulted in decreased sediment accumulation rate of the inner-shelf mud.